2018
DOI: 10.1002/jcp.27017
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐24‐3p regulates cell proliferation and milk protein synthesis of mammary epithelial cells through menin in dairy cows

Abstract: MiR‐24‐3p, a broadly conserved, small, noncoding RNA, is abundantly expressed in mammary tissue. However, its regulatory role in this tissue remains poorly understood. It was predicted that miR‐24‐3p targets the 3′ untranslated region (3′‐UTR) of multiple endocrine neoplasia type 1 (MEN1), an important regulatory factor in mammary tissue. The objective of this study was to investigate the function of miR‐24‐3p in mammary cells. Using a luciferase assay in mammary epithelial cells (MAC‐T), miR‐24‐3p was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The regulatory network between miR-24, MEN1, and menin was demonstrated also in other species, than humans, in vitro and in vivo [30][31][32]. Interestingly, Gao et al [30] demonstrated, both by Target Scan algorithm-based prediction and by an in vitro study Figure 1.…”
Section: The Autoregulatory Network Between Mir-24 Men1 and Menin: A Possible Effector Of Men1 Tumorigenesismentioning
confidence: 93%
See 1 more Smart Citation
“…The regulatory network between miR-24, MEN1, and menin was demonstrated also in other species, than humans, in vitro and in vivo [30][31][32]. Interestingly, Gao et al [30] demonstrated, both by Target Scan algorithm-based prediction and by an in vitro study Figure 1.…”
Section: The Autoregulatory Network Between Mir-24 Men1 and Menin: A Possible Effector Of Men1 Tumorigenesismentioning
confidence: 93%
“…The regulatory network between miR-24, MEN1 , and menin was demonstrated also in other species, than humans, in vitro and in vivo [ 30 , 31 , 32 ]. Interestingly, Gao et al [ 30 ] demonstrated, both by Target Scan algorithm-based prediction and by an in vitro study in neonatal rat cardiac myocytes, that miR-24 targets the CDNK1B mRNA, blocking translation of the encoded p27 kip1 protein, a negative regulator of cell cycle, resulting in a decreased G0/G1 arrest and in cell hypertrophy.…”
Section: The Autoregulatory Network Between Mir-24 Men1 and Menin: A Possible Effector Of Men1 Tumorigenesismentioning
confidence: 99%
“…miR-24-3p, which is abundantly expressed in mammary tissue, enhances proliferation. Through luciferase assays in immortalized bovine mammary epithelial cells (MAC-T), miR-24-3p has been shown to target the 3′UTR of Multiple endocrine neoplasia type 1 ( Men1 ) [ 156 ]. miR-101a is also able to regulate cell proliferation by altering Cyclooxygenase 2 ( Cox2 ) expression [ 127 ].…”
Section: Ncrnas In the Mammary Glandmentioning
confidence: 99%
“…Studies describing miRNAs involved in the expression of milk protein genes, such as casein ( miR-3031 [ 161 ], miR-15 [ 159 ], miR-139 [ 130 ], miR-101a [ 127 ], miR-142-3p [ 131 ]), have highlighted the aforementioned genes as markers of the differentiation status of mammary epithelial cells (see before) rather than with the goal of understanding the role of miRNAs in their regulation. Indirectly, by showing that miR-24-3p regulates genes involved in the PI3K/Akt/mTOR and JAK/Stat5 pathways, which regulate milk protein synthesis, Qiaoqiao et al [ 156 ] highlighted the importance of this miRNA in this process. miRNAs are also involved in milk calcium concentration.…”
Section: Ncrnas In the Mammary Glandmentioning
confidence: 99%
See 1 more Smart Citation